2023
DOI: 10.1371/journal.pone.0279533
|View full text |Cite
|
Sign up to set email alerts
|

Multilocus genotyping of Giardia duodenalis in pre-weaned calves with diarrhea in the Republic of Korea

Abstract: Giardia duodenalis is a protozoan parasite that infects humans, companion animals, livestock, and wildlife. Infections in cattle caused by this parasite are often asymptomatic, but such infections can cause diarrhea, reduced weight gain, and ill-thrift in young calves. Although G. duodenalis causes diarrhea in calves, only a few studies have been conducted on calves in the Republic of Korea (ROK). Here, we aimed to determine the prevalence and distribution of G. duodenalis assemblages in pre-weaned calves with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 63 publications
0
1
0
Order By: Relevance
“…Recently, a large number of studies have reported the prevalence of G. duodenalis in cattle in China, with a prevalence from 1.0% to 27.5% [ 16 , 33 , 34 , 35 , 36 , 37 ]. Moreover, in many other countries, such as Turkey, Argentina, and Korea, G. duodenalis infections in cattle have also been reported recently with a prevalence of 4.4–41.9% [ 15 , 38 , 39 ]. The overall G. duodenalis prevalence in calves in this study was 16.9% (74/438), which is similar to recent national and international reports.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a large number of studies have reported the prevalence of G. duodenalis in cattle in China, with a prevalence from 1.0% to 27.5% [ 16 , 33 , 34 , 35 , 36 , 37 ]. Moreover, in many other countries, such as Turkey, Argentina, and Korea, G. duodenalis infections in cattle have also been reported recently with a prevalence of 4.4–41.9% [ 15 , 38 , 39 ]. The overall G. duodenalis prevalence in calves in this study was 16.9% (74/438), which is similar to recent national and international reports.…”
Section: Discussionmentioning
confidence: 99%